Markets and Firms: Notes Towards the Future of Economic Sociology (translated by Maria Dobryakova) - WhiteHarrison С. (Journal of Economic Sociology, 2010)
The paper suggests an original approach to production markets considered as social constructions. A stylized model of pure competition is criticized. Within each market each producing organization learns how to seek a distinctive niche for its output commitments and product quality among a nest of peers. Active guidance comes from watching actions of these other peers as signals of that market. They reproduce themselves as molecules built from these ﬁ rms as atoms arranged in a linear way as an array of market niches. The paper describes general setting and a signaling mechanism around which the market molecule builds up. It also presents major results for an equilibrium model and its path dependencies. Finally, the paper explores possible switches in orientation along stream of goods and its evolutions over time.